P121 Surgical secondary cytoreduction in recurrent ovarian cancer patients with liver metastasis. (1st November 2019) - Conte, C; Gallotta, V; d'Indinosante, M; Capoluongo, E; Minucci, A; De Rose, A; Ardito, F; Giuliante, F; Di Giorgio, A; Zannoni, GF; Margreiter, C; Fagotti, A; et al.
Abstract : Introduction/Background: To describe accurately the oncological outcomes after hepatic resection (HR) in recurrent ovarian carcinoma (ROC) evaluating clinic-pathological variables and mutational status of BRCA1/2. Although HR is considered a challenging situation in ROC patients, assessment of BRCA1/2 mutational status seems to have a relevant clinical value to guide surgical therapy. Methodology: Patients who underwent HR for ROC at the Catholic University of Rome, between June 2012 and October 2017 were included. Exclusion criteria were represented by extra-abdominal disease and presence of diffuse peritoneal carcinomatosis requiring more than 2 bowel resections. Details relative to HR were collected and BRCA analysis was performed. Predictive factors for of post-relapse progression free survival (PHR-PFS)were assessed by univariate analyses using Cox-proportional hazard regression models. Results: Thirty-four patients undewent HR within secondary cytoreductive surgery (SCS). Six patients (17.6%) presented with hepatic relapse only, while the remaining 28 patients (82.4%) had concomitant extra-hepatic disease. In the whole series, the 3-yr PHR-PFS was 49.1% and the 3-yr progression free survival overall survivalwas 72.9%. Univariate analysis of variables conditioning PHR-PFS showed that only BRCA mutational status played a statistically significant favourable role: the 3-yr PHR-PFS rate was 81.0% in BRCA mutated patient compared to15.2% in wild type ones (p value: 0.001). Conclusion: Our clinical analyses suggest that in ROC patients with liver disease the assessment of BRCA mutational status can help to select patients elegible for SCS. Disclosure: Nothing to disclose.